2016
DOI: 10.1158/0008-5472.can-15-2926
|View full text |Cite
|
Sign up to set email alerts
|

MSH2 Dysregulation Is Triggered by Proinflammatory Cytokine Stimulation and Is Associated with Liver Cancer Development

Abstract: Inflammation predisposes to tumorigenesis in various organs by potentiating a susceptibility to genetic aberrations. The mechanism underlying the enhanced genetic instability through chronic inflammation, however, is not clear. Here, we demonstrated that TNFa stimulation induced transcriptional downregulation of MSH2, a member of the mismatch repair family, via NF-kBdependent miR-21 expression in hepatocytes. Liver cancers developed in ALB-MSH2 À/À AID þ , ALB-MSH2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Taking advantage of the lack of differentiation of PDCs into hepatocytes in the DDC-induced liver injury model, we investigated whether Epcam-positive PDCs could directly give origin to liver cancer. AID is upregulated in both hepatocytes and cholangiocytes in response to inflammatory stimulation (31,39,40) and elicits liver carcinogenesis through the induction of somatic mutations (34,41). AID-mediated mutagenesis in epithelial cells under inflammatory conditions is also attributed to inflammation-associated carcinogenesis in various organs (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of the lack of differentiation of PDCs into hepatocytes in the DDC-induced liver injury model, we investigated whether Epcam-positive PDCs could directly give origin to liver cancer. AID is upregulated in both hepatocytes and cholangiocytes in response to inflammatory stimulation (31,39,40) and elicits liver carcinogenesis through the induction of somatic mutations (34,41). AID-mediated mutagenesis in epithelial cells under inflammatory conditions is also attributed to inflammation-associated carcinogenesis in various organs (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…As a representative model of hepatocyte-derived HCC, we also examined HCCs developed in Alb Cre /AID cTg mice (Alb-derived HCCs) in which HCCs originated from albumin-expressing hepatocytes through AID-mediated mutagenesis (34). All of the Albderived HCCs were histologically consistent with well-to-moderately differentiated HCCs, and none of those tumors contained ductule-like components ( Supplementary Fig.…”
Section: Pdc-derived Hcc Displayed a Divergent Lineage Of Differentiamentioning
confidence: 99%
“…Some degree of MSI is known to be induced by chronic inflammation, as reported in pancreatitis [71] and ulcerative colitis [72]. We previously demonstrated that proinflammatory cytokine stimulation induced transcriptional downregulation of MSH2 via inflammation-mediated microRNA-21 expression in hepatocytes [14]. Furthermore, hepatocyte-specific disruption of MSH2 in mice results in the development of liver tumors with the histologic features of HCC.…”
Section: Msi Status and Treatment With Icis For Hepatocellular Carcinomamentioning
confidence: 94%
“…MSI reflects the condition of genetic hypermutability that results from impaired DNA MMR, and is accompanied by a 100-to 1000-fold increase in the mutation rate [10,12]. The presence of MSI is a sign of either sporadic or hereditary dysfunction of the MMR pathway caused by various factors, including mutations in MMR-related genes, inactivation of MMR gene transcription due to hypermethylation of its promoter region, or inflammation-mediated transcriptional repression [12][13][14].…”
Section: Microsatellite Instability and Cancer Predispositionmentioning
confidence: 99%
“…In fact, several types of congenital and acquired human cancers contain mutations or exhibit methylated silencing of DNA repair genes, including MLH1 and polymerase e (POLE) [132,133]. We recently demonstrated that the expression level of MSH2, a representative mismatch repair protein, is downregulated by tumor necrosis factor-a in inflamed hepatocytes [134]. In addition, hepatocyte-specific defects of MSH2 result in the development of liver tumors with the histologic features of HCC.…”
Section: Genetic Alterations Accumulated In Hepatitis Virusinfected Lmentioning
confidence: 99%